Minimal overshoot V-F control for islanded microgrids. (15th March 2021) - Bayoumi, Ehab H.E.; Soliman, Hisham M.; Soliman, Mostafa
Islanded microgrids' dynamics are greatly affected by the controllers' gains and power-sharing parameters. This paper considers an islanded microgrid containing two distributed generation (DG) units. Each DG has its pulse width modulated (PWM) inverter for three phases. Each inverter has two control loops in cascade. The inner loop is a current loop and the outer loop is a voltage loop. The controller of each loop is designed to provide good dynamic performance in terms of minimal percentage overshoot and overall system stability. The particle swarm optimisation (PSO) is used to design the current and voltage controllers to achieve the desired performance. The proposed controllers are compared with the conventional technique (Ziegler and Nichols), which shows the excellence of the proposed technique. Different test scenarios as voltage and current tracking and load parameters variation are used to examine the proposed design.